Khả năng khử khuẩn và phân hủy các chất bảo vệ thực vật của ozon - Nghị, Nguyễn Hoàng; Diệu, Trần Vĩnh; Yến Oanh, Đoàn Thị (Vietnam Journal of Chemistry, 2017)
Pesticides are used widely in agriculture that is a potential risk to cause pollution of water resource. Residual pesticide in vegetables and fruits during sparying process of plant protection chemicals is big problem in many countries. Right uses of pesticides (dosage, concentration of pesticide, period of spraying, moments of harvests…) provide conditions for their degradation under natural factors such as rain, UV radiation, time and so on. On other hands it is necessary to apply different methods for degradation and removal of residual pesticide in water, in vegetables and fruits (uncooked food) especially for family scale of uses. Besides problem of pesticide degradation, disinfection of drinking water and uncooked food also is a pressing requirement particularly for rural areas. According to FDA Federal Register Vol. 66, N.123 (2001), the Food and Drug Administration (FDA US) is amending the food additive regulations to provide for the safe use of ozone in gaseous and aqueous phases as an antimicrobical agent on food, including meat and poultry. As such the immersion and washing of uncooked food including meats in ozonated water is considered to be an effective method to remove residual pesticide in food. In last decades wide research on this topic in the world is recognized. In this work, we show the series of visual experiments on ability of ozone to degrade and remove pesticide in aqueous phase as well as microorganism like algae and fungi. Based on disinfection Chick-Watson law the pesticide degradation levels in water with and without ozonation is estimated in an animal testing by observing livetime of small loach-fish. Removal of algae in water and fungi in food by ozone is observed by optical microphotography. The standard test on Coliform and E. coli in ozone treated stagnant water has been carried out by Quatest 1. Keywords. Pesticide, residual, uncooked food, degradation, removal, ozone, ozonated water, disinfection Chick-Watson law, loach-fish, algae, fungi, Coliform, Quatest 1.